Modification of Coal Char-loaded TiO2 by Sulfonation and Alkylsilylation to Enhance Catalytic Activity in Styrene Oxidation with Hydrogen Peroxide as Oxidant - Mukhamad Nurhadi (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2017)
The modified coal char from low-rank coal by sulfonation, titanium impregnation and followed by alkyl silylation possesses high catalytic activity in styrene oxidation. The surface of coal char was undergone several steps as such: modification using concentrated sulfuric acid in the sulfonation process, impregnation of 500 mmol titanium(IV) isopropoxide and followed by alkyl silylation of n-octadecyltriclorosilane (OTS). The catalysts were characterized by X-ray diffraction (XRD), IR spectroscopy, nitrogen adsorption, and hydrophobicity. The catalytic activity of the catalysts has been examined in the liquid phase styrene oxidation by using aqueous hydrogen peroxide as oxidant. The catalytic study showed the alkyl silylation could enhance the catalytic activity of Ti-SO3H/CC-600(2.0). High catalytic activity and reusability of the o-Ti-SO3H/CC-600(2.0) were related to the modification of local environment of titanium active sites and the enhancement the hydrophobicity of catalyst particle by alkyl silylation.